ON THE ISSUE OF SAFETY OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS - N. Yu. Velts; T. M. Bukatina; E. O. Zhuravleva; G. V. Kutekhova; M. A. Darmostukova; Yu. V. Olefir; B. K. Romanov; S. V. Glagolev; V. A. Polivanov (Безопасность и риск фармакотерапии, 2018)
Non-steroidal anti-inflammatory drugs (NSAIDs) are liders in selling both in the Russian Federation and worldwide. The combination of  analgesic, anti-inflammatory and antipyretic effects make the drugs  of this group very popular in patients with various diseases. The  realization of NSAIDs in pharmacies occurs both by prescription and  over-the-counter, so the safety assessment of the use of this group  of drugs remains relevant. In the current practice, self-administration (responsible selfmedication) of drugs of the NSAID  group is an additional factor affecting the safety of their intake. According to the studies, about 40 % of patients taking  NSAIDs consider that NSAIDS are absolutely safe, and more than 30  % of those taking OTC NSAIDs use them in excess of the  recommended dosages. We analyzed 3963 individual case safety  reports (ICSR) in the federal database «Pharmacovigilance» from  07.12.2008 to 31.08.2017. The inclusion criterions was the presence of information on the off-label application of NSAIDs in the ICSR,  reports of adverse effects that may be associated with the use of this drug or erroneous reports on the active substance, which was  not present in this drug. The most frequent mistakes in the  application were an increase of the daily dose, a change in the  method of administration to patient who are contraindicated with this drug. There were 9 ICSR of burning sensation in the anus with the  introduction of ibuprofen suppositories (not in the label), and 7 ICSR  of ineffectiveness of the active substance, which was not present in this drug.